SNARE proteins synaptobrevin, SNAP-25 and syntaxin are involved in rapid and slow endocytosis at synapses - Xu, Jianhua (2013)
Rapid endocytosis, which takes only a few seconds, is widely observed in secretory cells. Although it is more efficient in recycling vesicles than slow clathrin-mediated endocytosis, its underlying mechanism, thought to be clathrin-independent, is largely unclear. Here we reported that cleavage of three SNARE proteins essential for exocytosis, including synaptobrevin, SNAP-25 and syntaxin, inhibited rapid endocytosis at the calyx of Held nerve terminal, suggesting the involvement of three SNARE proteins in rapid endocytosis. These SNARE proteins were also involved in slow endocytosis. In addition, SNAP-25 and syntaxin facilitated vesicle mobilization to the readily releasable pool, likely via their roles in endocytosis and/or exocytosis. We concluded that both rapid and slow endocytosis share the involvement of SNARE proteins. The dual role of three SNARE proteins in exo- and endocytosis suggests that SNARE proteins may be molecular substrates contributing to the exo-endocytosis coupling, which maintains exocytosis in secretory cells.